215k views
2 votes
Examine Morgan’s work to solve the equation. -8m + 6 - 2m = 9(3m + 4) + 5m 1.  -8m + 6 - 2m = 27m + 36 + 5m 2.  -10m + 6 = 32m + 36 3.  6 = 22m + 36 4.  -30 = 22m 5.  −15 11 = m What is the error in Morgan’s work? She did not distribute the 9 to both terms inside the parentheses. She combined the like terms on each side of the equation wrong. She applied the addition property of equality to isolate the variable term wrong. She applied the division property of equality instead of the multiplication property of equality to solve for the variable.

User Jassinm
by
4.5k points

2 Answers

4 votes

Answer:

She applied the addition property of equality to isolate the variable term wrong.

C

The third one.

Explanation:

Examine Morgan’s work to solve the equation.

-8m + 6 - 2m = 9(3m + 4) + 5m

1. -8m + 6 - 2m = 27m + 36 + 5m

2. -10m + 6 = 32m + 36

3. 6 = 22m + 36

4. -30 = 22m

5.

−15

11

= m

What is the error in Morgan’s work?

She did not distribute the 9 to both terms inside the parentheses.

She combined the like terms on each side of the equation wrong.

She applied the addition property of equality to isolate the variable term wrong.

She applied the division property of equality instead of the multiplication property of equality to solve for the variable.

User Chris Uzdavinis
by
5.0k points
2 votes

Answer:

(C)She applied the addition property of equality to isolate the variable term wrong.

Explanation:

Morgan's Work to solve
-8m + 6 - 2m = 9(3m + 4) + 5m is set out below:


-8m + 6 - 2m = 9(3m + 4) + 5m \\1. -8m + 6 - 2m = 27m + 36 + 5m \\2.-10m + 6 = 32m + 36 \\3. 6 = 22m + 36 \\4.-30 = 22m \\5.-15 11 = m

In Step 3, Morgan applied the addition property of equality to isolate the variable term wrong.

She should have had:


-10m+10m+6=32m+10m+36\\

Which then gives the result of Step 3 to be


6=42m+36

Solving

6-36=42m

-30=42m


m=-(30)/(42) \\=-(5)/(7)

User Matthew Kerian
by
5.3k points